2015
DOI: 10.1128/aac.00662-15
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between GyrA Substitutions and Ofloxacin, Levofloxacin, and Moxifloxacin Cross-Resistance in Mycobacterium tuberculosis

Abstract: The newer fluoroquinolones moxifloxacin (MXF) and levofloxacin (LVX) are becoming more common components of tuberculosis (TB) treatment regimens. However, the critical concentrations for testing susceptibility of Mycobacterium tuberculosis to MXF and LVX are not yet well established. Additionally, the degree of cross-resistance between ofloxacin (OFX) and these newer fluoroquinolones has not been thoroughly investigated. In this study, the MICs for MXF and LVX and susceptibility to the critical concentration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 38 publications
1
37
0
Order By: Relevance
“…Our findings underscore the possibility of evaluating later-generation quinolones for the treatment of ofloxacin-resistant TB (33,34) and as a salvage therapy in patients with MDR-TB (35). In addition, our results imply that susceptibility to OFX may not necessarily indicate susceptibility to all quinolones when OFX is used as a representative quinolone in susceptibility testing (17). We thus suggest that the susceptibility to each quinolone should be tested as recommended by WHO (36) because the quinolones are not completely cross-resistant.…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…Our findings underscore the possibility of evaluating later-generation quinolones for the treatment of ofloxacin-resistant TB (33,34) and as a salvage therapy in patients with MDR-TB (35). In addition, our results imply that susceptibility to OFX may not necessarily indicate susceptibility to all quinolones when OFX is used as a representative quinolone in susceptibility testing (17). We thus suggest that the susceptibility to each quinolone should be tested as recommended by WHO (36) because the quinolones are not completely cross-resistant.…”
Section: Discussionmentioning
confidence: 62%
“…Similarly, other studies have reported that clinical isolates carrying D94G exhibit higher levels of resistance to OFX, MXF, and GAT than isolates carrying A90V or D94A (16,17,38). Recently, Rigouts et al showed strong evidence for a higher rate of failure/relapse in the presence of the D94G mutation (70.0%) than in that of the D94A mutation (11.1%) when patients were treated with GAT (38).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…We usually sequenced isolates recovered from the drug-free LJ slopes, but where no resistance mutations were found in phenotypically resistant strains, sequencing was repeated with isolates recovered from the OFX-containing LJ slope to detect low-frequency mutations (8, 9). Strains belonging to the East Asian lineage were identified on the basis of RD105 (10).…”
Section: Methodsmentioning
confidence: 99%